Status Of Rice Blast In Sundarban Region Of West Bengal, India (Journal of Plant Disease Sciences, 2020)
Sundarbans, the southern-most part of West Bengal under ‘Coastal and Saline Agro-ecological Zone’ and the largest delta on the planet is one of the most unique regions. The agrarians economy of sundarbans was primarily donomated by rice based farming system, where generally rice-rice-follow system has been practiced year after year. For better understanding of the rice blast disease scenario, survey was conducted in farmers’ fields of selected ten blocks of Sundarbans viz.Kakdwip, Namkhana, PatharPratima, Kultali, Joynagar-I, Basanti, Gosaba, Hingalganj, Sandeshkali-I, and Sandeshkhali-II during Kharif, 2016 and 2017 (July to November) and Rabi 2016-17 and 2017-18 (December to May) at growth stage 2 (Tillering), 4 (Booting), and 8 (Flowering) for leaf blast, and 9 (mature grain) for neck blast. Maximum leaf blast severity during Kharif season was observed at Hingalganj (23.81%) followed by Namkhana (23.56%) and Kultali (23.46%). Minimum leaf blast severity was observed at Sandeshkali-I (17.38%). The maximum neck blast incidence was found at Namkhana (4.82%) and least was found at Sandeshkali-I (1.62%). During Boro season, it has been found that the leaf blast severity was maximum and the mean PDI was 45.02 in Kakdwip. Next in order was Basanti with a mean PDI of 42.96% followed by Gosaba (42.18%). Minimum leaf blast severity with a mean PDI of 31.75% was recorded in Hingalganj. Maximum incidence of neck blast was observed at Gosaba (20.44%) followed by Kakdwip (18.80%) and Basanti (18.43), while least incidence of neck blast was observed at Hingalganj (12.12%). This is a comprehensive attempt to know the present scenario of the disease in Sundarban region of West Bengal that will help to the researchers and extension workers for further progress of the works in future.
Keywords: Rice; Blast; W. bengal Incidence